1992
DOI: 10.1111/j.1651-2227.1992.tb12178.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic adult granulosa cell tumor causing precocious pseudopuberty in a six‐year‐old girl

Abstract: A very rare occurrence of adult granulosa cell tumor of the ovary (not of the juvenile type) causing precocious pseudopuberty in a six-year-old girl is described. An additional feature of interest was that the tumor appeared entirely cystic. To our knowledge, this condition in such a young premenarchal patient has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
2
5
0
1
Order By: Relevance
“…Most of the tumours were clinically and radiologically stage-I at time of diagnosis as reported in other studies (Arisaka et al, 1992;Till and Schmidt, 2005;Ferrari et al, 2007), however two were FIGO stage II. On gross examination, the JGCT and SST were frequently cystic as shown in the figure; however other types were predominantly solid masses.…”
Section: Discussionsupporting
confidence: 58%
“…Most of the tumours were clinically and radiologically stage-I at time of diagnosis as reported in other studies (Arisaka et al, 1992;Till and Schmidt, 2005;Ferrari et al, 2007), however two were FIGO stage II. On gross examination, the JGCT and SST were frequently cystic as shown in the figure; however other types were predominantly solid masses.…”
Section: Discussionsupporting
confidence: 58%
“…2 To contrast our findings with the natural response of the labia minora to exposure to a high concentration of estrogen in a prepubertal girl with normal IGF-I, we show an image of a hugely enlarged labia minora of a different patient (Figure 3). 10 In the patient described in the current report, the thickened hymen was consistent with the elevated level of circulating estradiol. Hymenal morphology is dependent on estrogen status, 11 and thus it seems that GH deficiency has no influence on hymenal growth.…”
Section: Discussionsupporting
confidence: 61%
“…In the present case, the microscopic features of the ovarian tumor, particularly the mature follicles with Call-Exner bodies, were definitely consistent with those of AGCT. Arisaka et al 1 reported a patient with an AGCT which was entirely cystic, in a 6 year-old girl. Zaloudek et a 1.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant ovarian tumors are responsible for 2-3% of all cases of precocious pseudopuberty (PP) in girls 1 features of granulosa cell tumors that occur frequently in young girls, so-called juvenile granulosa cell tumors (JGCT), differ histologically from those occurring in adults. As a cause of PP in young girls, adult type granulosa cell tumors (AGCT) are extremely rare'.…”
Section: Introductionmentioning
confidence: 99%